PD-L1 expression in Triple Negative Breast Cancer: a study of an Iraqi population - Keorges, Gina James (Journal of Medical Science, 2023)
Introduction. Breast cancer is the second most common cause of cancer death in women. Breast cancer awareness has increased due to mammography screening.Aim. The study aims to evaluate the prevalence of the anti-programmed death-ligand 1 (PD-L1) expression in triple-negative breast cancer (TNBC) cases and to correlate it with clinicopathological parameters.Material and methods. This retrospective study investigates 44 triple-negative breast cancer cases. PD-L1 expression was measured by an immunohistochemical technique using Dako kits, PD-L1 IHC 22C3 pharm Dx on 44 paraffin block samples from Duhok Municipal Laboratories. If the specimen has a combined positive score (CPS) of 10 or higher, it expresses PD-L1. Age groups, grades, types, stages, and lymph node status are studied.Results. The mean age of the 44 patients was 47.7 years. 54.5% of the patients were in the middle age group, 63.6% were in grade III, 88.6% had invasive ductal carcinoma, and 75% were negative for PD-L1. 63.6% of the patients had the nuclear protein Ki67 (Ki-67) less than 20. 70.5% of the patients were in stage T2, and 45.5% had N1 lymph node status. There is a significant association between PD-L1 and Ki67. All patients with positive PD-L1 had Ki67 more than 20, while only 15.2% of the patients with negative PD-L1 had Ki67 more than 20.Conclusion. Most TNBC patients are middle age, have grade III, and 75% have negative PD-L1. There is a significant association between PD-L1 and Ki-67. All patients with positive PD-L1 have Ki67 of more than 20.
Keywords: expression; PD-L1; triple negative; breast cancer